Intraarticular Inflammation and Catabolic Markers in Femoroacetabular Impingement during Progression of Disease -comparison between early and late stage disease-. Issue 7 (31st July 2020) - Haneda, Masahiko; Clohisy, John; Rai, M. Farooq; O'Keefe, Regis; Brophy, Robert; Pascual-Garrido, Cecilia
Objectives: Femoroacetabular impingement (FAI) has been proposed as an etiologic factor in up to 50% of osteoarthritis hips (OA). Inflammation is thought to be one of the main initiators of hip OA, yet little is known about the location and progression of intraarticular inflammation in FAI hips. The aim of this study is to characterize inflammation and catabolic markers in the early and late stage of FAI hips in patients with symptomatic Cam FAI. Methods: Head-neck cartilage, acetabular cartilage, and synovial samples were obtained from 30 patients undergoing hip surgery. Fifteen patients had a diagnosis of symptomatic Cam FAI (early FAI-symptomatic FAI) and 15 presented with advanced OA secondary to Cam FAI (late FAI/secondary OA). Control cartilage samples were procured from the head-neck junction of 7 osteochondral fresh allografts from healthy young-adult donors (control). Radiographically, the α-angle was utilized to confirm hip impingement and Tönnis grade was used to define pre-OA (Tönnis grade 0-1) and advanced OA (Tönnis grade >2). Safranin O stained sections were used to assess cartilage degeneration using the Mankin score. Immunostaining of IL-1β, MMP-13, ADAMTS-4, type II collagen (COL2), and the NITEGE aggrecan neoepitote was performed to evaluate inflammation and catabolic markers. Quantification of immunopositive cells was performed and one-way analysis of variance with Tukey's post hoc test was applied to analyze differences between groups. Results: Characteristics of the study participants are presented in Table 1. Cartilage from the impingement zone (head-neck and acetabulum) of hips with early and late FAI showed microscopic osteoarthritic degenerative changes. Compared to control, head-neck cartilage from early and late stage FAI hips highly expressed inflammatory and catabolic markers IL-1β (69.7±18.1, 72.5±13.2 vs 20.2±4.9), MMP-13 (79.6±12.6, 71.4±18.8 vs 25.3±9.5), ADAMTS-4 (83.9±12.2, 82.6±12.5 vs 24.3±11.1), NITEGE (89.7±7.7, 95.7±4.7 vs 39.8±20.5) (p<0.05). Expression for COL2 was similar among groups (93.6±3.9, 92.5±5.8 vs 95.4±6.4, p=0.4892). Finally, percent of immunopositive cells for IL-1β, MMP-13, ADAMTS-4, and ACAN were positively correlated with Mankin score (r=0.52-0.75; p<0.001). The percentage of immunopositive cells present in acetabular cartilage was similar in both early and late FAI (IL-1β: 83.3 ± 24.8, 80.7 ± 15.6, 80.9 ± 26.3, p = 0.9571; MMP-13: 94.3 ± 9.7, 85.2 ± 12.3, 93.3 ± 10.3, p = 0.0653; ADAMTS-4: 98.5 ± 2.3, 98.4 ± 3.4, 99.2 ± 3.0, p = 0.6997, COL2: 99.8 ± 0.7, 99.7 ± 1.1, 98.6 ± 3.6, p = 0.3830). Additionally, inflammatory and catabolic markers were secreted to the ECM (extracellular matrix) in late FAI but not in early FAI. (Figure 1) Synovitis was minimal in early FAI but severe in late FAI. The average synovitis score was lower in early FAI than late FAI (2.5 ± 1.7, 4.4 ± 1.6; p=0.0086). Lower IL-1β expression levels were noted in synovium from early FAI compared to late FAI (p=0.001). Conclusion: Osteoarthritic degenerative changes, inflammation and catabolic markers are evident in the cartilage from the head-neck and acetabulum (impingement zone) in patients with hip FAI morphology during early and late stage disease. In late disease, increase expression of these markers are also observed in the ECM. Severe synovitis, however, was only evident in late stage disease. This study defines joint specific location and timing of inflammation relative to the disease process, suggesting the impingement area is a potential mediator of inflammation and joint degeneration during disease progression.